Global Value Chain Upgrading - Tobias Ylömäki (The Research Institute of the Finnish Economy (ETLA), 2016)
Global value chain (GVC) upgrading is a key factor in country-level economic performance. Therefore it is important to study its fundamental, firm-level origins. What are the main attributes that drive firms toward GVC upgrading? How do upgrading trajectories differ? The previous literature has largely concentrated on developing countries and firms producing low value-added goods and services. Are there any fundamental differences between these and firms in a highly developed country that mainly operate in sectors other than pure manufacturing? I answer these questions by analyzing a 2015 survey that consists of thousands of Finnish firms from a variety of industries and size cohorts. From the survey, it is possible to determine firms' ex ante propensity for GVC upgrading. I found that innovativeness, the young age of the firm and outsourcing positively affect upgrading. I also found that firms do not plan their upgrading via any specific trajectory.
Keywords: 330; Global value chain upgrading; firm-level survey analysis; innovativeness; outsourcing